Linear Endobronchial Ultrasound: What's New? - He, Tao; Mehta, Atul C. (Seminars in Respiratory and Critical Care Medicine, 2018)
Since its advent more than a decade ago, real-time linear endobronchial ultrasound (EBUS) guided transbronchial needle aspiration has revolutionized the diagnosis and staging of nonsmall cell lung cancer (NSCLC), and has become the standard of care with widespread acceptance. It is also extensively used to diagnose other disease entities such as malignancy besides NSCLC, benign diseases, or infectious processes. Ancillary studies have shown its superior safety profile and cost-effectiveness. In recent years, linear EBUS has been expanding its clinical applications owing to the emerging new tools such as the 19-gauge (19G) needle and miniforceps. Meanwhile, with several ground-breaking discoveries in lung cancer treatment over the past few years, linear EBUS has found its way to fit into this scheme as a safe and effective diagnostic tool. This review summarizes the most recent evidence on evaluating the performance of linear EBUS-guided biopsy in various clinical situations.
Keywords: linear endobronchial ultrasound; needle aspiration; 19G needle; miniforceps; targeted therapy; immunotherapy; rebiopsy; next generation sequencing